Performance of aerogel as a thermal insulation material towards a sustainable design of residential buildings for tropical climates. - Bashir, Aminu Wali (2021)
The building sector accounts for nearly 40% of global energy consumption with an anticipation of a continuous increase in the coming decades. Energy efficiency measures through the adoption of thermal insulation materials are tools that could crash the peak demand for energy in buildings while improving their thermal comfort. Aerogel is then considered to be the most effective material for insulation, owing to its unique thermal properties. This research presents a study on the performance of aerogel as a thermal insulation material towards a sustainable design of residential buildings for tropical climates of Lagos, Nigeria, and Belém-Pará, Brazil. The aim was to examine its performance in terms of thermal comfort improvement and energy consumption reduction against the conventional materials utilized in constructing residential buildings in the selected locations. A residential building design comparable to both selected locations was selected and modeled with common conventional materials utilized in the selected locations as base variants. Then the models were later modified by including aerogel blanket on various surfaces of the models. Major parameters that influence indoor environmental quality were measured through building energy simulations and the results obtained in both cities were compared to standard recommended values. Also, their corresponding energy consumption and tariff charges are reported. Results showed that in Lagos, the proposed insulation material had the highest influence when inserted in the attic and floor slabs of the designed model, while in Belém, the insulation material had the highest significance when inserted on the external façades. In terms of thermal comfort improvement, it can be concluded that aerogel had more significance in Lagos than in Belém, while concerning energy consumption reduction, the insulation material had more influence in Belém than in Lagos. Aerogel demonstrated significant potential for both thermal comfort improvement and energy consumption reduction in both selected locations. However, further research may be necessary to effectively conclude the performance of the proposed insulation material in the selected locations. The findings in this study provide a stepping-stone for the design and construction of efficient & sustainable residential buildings for tropical climates in Nigeria and Brazil.